Constructing a non-foundational theological approach to Christian ethics - Oudtshoorn, David A. van (HTS teologiese studies, 2015)
Postmodernism challenges the idea of any foundational truth on which theoretical and operational systems may be built. This has led to a meta-ethical revision of the resuppositions underlying different ethical systems. This article offers a meta-ethical critique of the possibility of constructing a Christian ethical system. It is argued that the general concept of ethics cannot be used as a foundation on which to build any Christian ethical system, as the Christian faith opposes a number of key meta-ethical assumptions for ethics. At the same time Christianity must be careful not to isolate itself from rational ethical debates through succumbing to the temptation of fideism. While the Christian faith may utilise certain ethical categories, and must permit itself to be judged by other ethical systems, it also has to develop its own unique response to reflect the faith, hope and love which the good news of Christ offers to broken sinners in a broken world.